Investigation of steam and CO2 gasification for biochar using a circulating fluidized bed gasifier model in Aspen HYSYS - ÖZVEREN, UĞUR (My University, 2022)
Researchers are focusing their efforts on renewable energy sources to avoid future global energy and environmental crises. One of the renewable energy sources, biomass, can be processed using a variety of techniques and thermodynamic cycles. Biomass gasification, for example, has several environmental and technical benefits. Biochar, on the other hand, is produced by the use of a thermal pretreatment technique to biomass, and it can be used to overcome the drawbacks of biomass in gasification operations. Despite the fact that biochar improves the quality and volume of syngas, there is a few research on this topic in the literature. Although researchers have used a variety of process simulators, the number of gasification systems developed in the Aspen HYSYS simulator is very limited, and no circulating fluidized bed (CFB) gasification model for biochar gasification has ever been reported to our knowledge. Based on the non-stoichiometric equilibrium technique, a unique CFB gasifier model was developed in this work. The impacts of various operating parameters on the syngas were evaluated. In addition, the gasification performance of 10 biochar samples with varying physicochemical features was compared to the physicochemical qualities of solid fuels in a steam and CO2 mixture. As a result, biochar samples with a high carbon content formed an H2-rich syngas with a high calorific value during steam gasification. According to parametric studies, the optimum gasification temperature is about 700 ◦C, the optimum gasification pressure is 1 bar, and the optimum ratios of steam/biochar and CO2/biochar are between 0.2–0.3 and 0.5–1.0, respectively.
Keywords: Kimya Mühendisliği ve Teknolojisi; Kimya; Biyokimya; Alkoloidler; Temel Bilimler; Mühendislik ve Teknoloji; Chemical Engineering and Technology; Chemistry; Biochemistry; Alcaloides; Natural Sciences; Engineering and Technology; KİMYA, MULTİDİSİPLİNER; Temel Bilimler (SCI); MÜHENDİSLİK, KİMYASAL; Mühendislik; Mühendislik, Bilişim ve Teknoloji (ENG); CHEMISTRY, MULTIDISCIPLINARY; CHEMISTRY; Natural Sciences (SCI); ENGINEERING, CHEMICAL; ENGINEERING; Engineering, Computing & Technology (ENG); Genel Mühendislik; Kimyasal Sağlık ve Güvenlik; Akışkan Akışı ve Transfer İşlemleri; Kimya (çeşitli); Kimya Mühendisliği (çeşitli); Mühendislik (çeşitli); Genel Kimya Mühendisliği; Kolloid ve Yüzey Kimyası; Genel Kimya; Kataliz; Fizik Bilimleri; General Engineering; Chemical Health and Safety; Fluid Flow and Transfer Processes; Chemistry (miscellaneous); Chemical Engineering (miscellaneous); Engineering (miscellaneous); General Chemical Engineering; Colloid and Surface Chemistry; General Chemistry; Catalysis; Physical Sciences; CO2 Gasification; Steam Gasification; Biochar; Fluidized Bed Gasifier; Aspen HYSYS; BIOMASS GASIFICATION; HYDROGEN-PRODUCTION; COAL-GASIFICATION; AIR GASIFICATION; PERFORMANCE ANALYSIS; ENERGY-CONSUMPTION; PROCESS SIMULATION; SYNGAS PRODUCTION; WASTE; PLUS; CO2 Gasification; Steam Gasification; Biochar; Fluidized Bed Gasifier; Aspen HYSYS